Analisis Faktor Kritis Keberhasilan pada Implementasi E-Procurement - Suryani, Eli (Bina Nusantara University, 2011)
The purpose of this study is to analyze the Critical Success Factor of e-procurement implementation, that is able to show the influence factors of successful implementation of e-procurement in companies. This study uses benchmarking method to examine the non-random selected samples from some companies which are advanced in implementing e-procurement including the contextual analysis of issues related to similar situations. From the findings then performed the identification and benchmarking study, mapping towards the successful practice at the companies. Eventually it is concluded that there is no best standard for e-procurement as the factors most affecting successful implementation are non-technical, of which this understanding will be the first step to systematically analyze the supporting factors in implementing e-procurement successfully. Therefore, e-procurement does not only improve the operational performance of the company in efficiency improvement of enterprise's supply chain management process but also provide added value for the company.